THE EFFECTIVENESS OF USING E-BOOK MEDIA ON ADOLESCENTS' KNOWLEDGE ABOUT HIV/AIDS AT SMAN 1 TASIKMALAYA - Daffa Afib Nugraha; Peni Cahyati; Heri Djamiatul Maulana (Jurnal Medika Cendikia, 2023)
Introduction: Adolescence is one of the potentials to become a much better generation, it is very important to provide knowledge to adolescents about deviant behavior such as drugs, sexual intercourse that can lead to transmission of HIV-AIDS. The spread of the HIV/AIDS virus occurs due to a lack of knowledge among adolescents, as well as inappropriate community behavior. Health education aims to increase awareness of the disease and prevent the transmission of HIV/AIDS. E-Book is an educational media in the form of digital books that can be opened through a computer or gadget. Objective: This study aims to determine the effectiveness of the use of E-Book media on adolescents' knowledge about HIV/AIDS at SMAN 1 Tasikmalaya. Methods: This research design uses quantitative methods with pre-experiment with one group pretest posttest design. With Simple Random Sampling technique totaling 67 respondents. Data analysis was carried out by univariate and bivariate methods, namely Skewnes and kurtosis tests with a significant level between -2 and +2. Results: The results showed that the level of knowledge before and after health education using E-Book media increased with an average of 58.64 to 72.64. Data analysis shows a p value of 0.000 <0.05, this indicates that the p value is smaller than α, so it is said that the research hypothesis is accepted. Conclusion: E-Book media is effective in increasing adolescent knowledge about HIV/AIDS.